2004
DOI: 10.4049/jimmunol.172.4.2549
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Antigen-Primed CD8+ T Cells to the Development of Airway Hyperresponsiveness and Inflammation Is Associated with IL-13

Abstract: The role of Th2/CD4 T cells, which secrete IL-4, IL-5, and IL-13, in allergic disease is well established; however, the role of CD8+ T cells (allergen-induced airway hyperresponsiveness (AHR) and inflammation) is less clear. This study was conducted to define the role of Ag-primed CD8+ T cells in the development of these allergen-induced responses. CD8-deficient (CD8−/−) mice and wild-type mice were sensitized to OVA by i.p. injection and then challenged with OVA via the airways. Compared with wild-type mice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 61 publications
9
93
0
Order By: Relevance
“…Our data are in line with recent studies reporting on the effector role of CD8 ϩ T cells in allergic asthma (30,31) and strongly support the idea that the CD4 ϩ Th2 dogma in allergic diseases should be revisited (7). However, although the results presented come from a representative mouse model, studies in humans are required to confirm the hypothesis that CD8 ϩ T cells are involved in the development of AD skin lesions.…”
Section: Discussionsupporting
confidence: 92%
“…Our data are in line with recent studies reporting on the effector role of CD8 ϩ T cells in allergic asthma (30,31) and strongly support the idea that the CD4 ϩ Th2 dogma in allergic diseases should be revisited (7). However, although the results presented come from a representative mouse model, studies in humans are required to confirm the hypothesis that CD8 ϩ T cells are involved in the development of AD skin lesions.…”
Section: Discussionsupporting
confidence: 92%
“…The effects of this cytokine are broad, including mucus production, increased responsiveness of airway smooth muscle to acetylcholine, and secretion of matrix metalloproteases and cysteine proteases, involved in lung remodeling. It was recently shown that IL-13 alone from CD8 + T cells was sufficient to cause AHR in OVA-sensitized mice [33,34]. The present data suggest that it is a combination of IL-13 and IL-4 from CD8 cells that mediate an airway response.…”
Section: Discussionsupporting
confidence: 63%
“…PE-conjugated anti-mouse Gr-1 and allophycocyanin-conjugated CD11c were used to identify plasmacytoid DCs. The stained cells were washed, resuspended in PBS, and then analyzed by flow cytometry (FACSCalibur) as previously described (32). The numbers of CD11c ϩ and CFSE ϩ cells in BAL, PBLN, and lungs were derived by multiplying the percentage of stained cells by the total number of cells isolated.…”
Section: Flow Cytometrymentioning
confidence: 99%